Design and construction of an interrogation unit for fiber Bragg grating sensor system - Mohd. Akil, Mohd. Asmu’I (2009)
Fiber optic sensors are commonly used nowadays in civil structure and medical applications as well as in research. This is due to the ability of fiber optic sensors exceeding the ability of other sensors in terms of sensitivity, precision and the ability to be multiplexed in a large network of sensors such as for a large area landslide monitoring. One popular applications of fiber optic technology is the use of in core Fiber Bragg grating (FBG). FBG sensors are very sensitive to parameters such as strain and temperature. Unfortunately the high sensitivity demanded interrogation system that has the same resolution capability. This thesis mainly discusses on the development of an interrogation system for FBG using a wavelength filter method. The works also cover a simulation coding program using Matlab® that has been developed for a tunable filter around 1310 nm to studies the characteristics of a Fabry Perot (FP) filter. The complete interrogation system based on wavelength filter method is developed using other optical components including broadband source, coupler, wavelength filter and photodetector. The photodetector and wavelength filter are interface to a personal computer (PC) for the purpose of tuning at a certain wavelength and photodetector collecting the optical power. By scanning the whole spectrum and collecting the power of each individual wavelength, ?; the ?Bragg from the sensor can be identified. This is achieved by using an RS-232 interface protocol and a software utilizing Microsoft Visual Basic 6.0. The design software governs the whole process of controlling the wavelength filter and the collection of power from photodetector. The Bragg wavelength, ?Bragg, is easily known via an algorithm developed by comparison method. This setup can be used in any sensing system based on FBG such as temperature and strain monitoring with the resolution of 0.1nm. This system gives a Bragg wavelength, ?Bragg with a standard deviation of 1.2% compare to the OSA value. Finally the system was tested using FBG with a given strain. The result produced indicated a linear trendline which is similar to that obtained on OSA with a linear regression of 99.77%.